Integrasi Teknologi Digital dalam Pembelajaran STEAM di Sekolah Dasar: Analisis Bibliometrik Publikasi Scopus 2016-2025 - Ahmad, Zulfa Nafisah; Kurniawan, Muhammad Ragil (Universitas Muhammadiyah Magelang, 2026)
This study aims to map the development, thematic structure, and emerging research trends related to the integration of digital technology in STEAM learning at the primary school level through a bibliometric approach. Data were collected from Scopus-indexed publications published between 2016 and 2025 and analyzed using Bibliometrix R-Package and VOSviewer. The analysis examined publication growth, subject area distribution, patterns of authorship and international collaboration, and keyword co-occurrence to identify thematic clusters and research dynamics. The findings indicate a steady growth of publications with a strong interdisciplinary orientation, primarily involving social sciences, computer science, and engineering. Thematic mapping reveals a noticeable shift from the use of digital technology as a supportive learning tool toward its role as a pedagogical component in developing computational thinking, interactive digital learning environments, and 21st-century competencies within primary STEAM education. Emerging topics such as artificial intelligence, game-based learning, robotics, and teacher-related pedagogical design have gained increasing attention in recent years, although their conceptual integration within a holistic STEAM framework remains limited. Overall, this study provides a comprehensive overview of the current research landscape and highlights evolving directions in digital technology–integrated STEAM education at the primary level.